2020
DOI: 10.47552/ijam.v11i4.1727
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on Efficacy of Vishakalpa (Shwetra lepa) in Shwetra (Vitiligo)

Abstract: Shwetra (Vitiligo) is a skin disease which takes longer time to cure. It affects the external beauty of the body causing social stigma, shyness, loss of confidence, fear of comments marital problems, etc. The disease needs repeated shodhana and regular internal and external shaman chikitsa for longer duration. Objectives: To study the efficacy of Vishakalpa (Shwetra lepa) alone in the management of Shwetra and to provide a potent drug for sure and quick relief from Shwetra (vitiligo), this pilot study was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The dosage and frequency will be suggested at the outset and following clinical assessment, the researcher expects to establish the efficacy, acceptability and outcome of the proposed poly herbal Hair pack and Gel formulation (of dosage and frequency of application). Studies on efficacy of different Ayurvedic preparations were reported [28][29][30]. Few of the related studies were reviewed [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The dosage and frequency will be suggested at the outset and following clinical assessment, the researcher expects to establish the efficacy, acceptability and outcome of the proposed poly herbal Hair pack and Gel formulation (of dosage and frequency of application). Studies on efficacy of different Ayurvedic preparations were reported [28][29][30]. Few of the related studies were reviewed [31][32][33].…”
Section: Discussionmentioning
confidence: 99%